H4-alkanes: A new class of hydrogen storage material?. (26th January 2017) - Harrison, D.; Welchman, E.; Thonhauser, T.
Abstract: The methane-based material (H2 )4 CH4, also called H4M for short, is in essence a methane molecule with 4 physisorbed H2 molecules. While H4M has exceptionally high hydrogen storage densities when it forms a molecular solid, unfortunately, this solid is only stable at impractically high pressures and/or low temperatures. To overcome this limitation, we show through simulations that longer alkanes (methane is the shortest alkane) also form stable structures that still physisorb 4 H2 molecules per carbon atom; we call those structures H4-alkanes. We further show via molecular dynamics simulations that the stability field of molecular solids formed from H4-alkanes increases remarkably with chain length compared to H4M, just as it does for regular alkanes. From our simulations of H4-alkanes with lengths 1, 4, 10, and 20, we see that e.g. for the 20-carbon the stability field is doubled at higher pressures. While even longer chains show only insignificant improvements, we discuss various other options to stabilize H4-alkanes more. Our proof-of-principle results lay the groundwork to show that H4-alkanes can become viable hydrogen storage materials. Highlights: Developed new class of materials, H4-alkanes, based off of extending H4M. Performed evolutionary structure search using LAMMPS to determine structures. Determined melting temperatures over range of pressures using MD simulations. Found that longer H4-alkanes show increased stability at higher pressures.